Anterior Temporal Lobectomy in Refractory Complex Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The outcome of 22 patients with onset of complex partial seizures (CPS) in early childhood and treated by anterior temporal lobectomy after intervals varying from three to 28 years, is reported from the Epilepsy Research Center, Baylor College of Medicine, Houston, TX.